Migraine consultation and treatment in the era of COVID-19 - Ryliškienė , K. (Neurologijos seminarai, 2020)
During the COVID-19 pandemic, patients have limited access to scheduled visits and emergency departments; these limitations compromise the optimal care of migraine. This article reviews teleconsultation options, patient preparation for counselling, safe use of acute and preventive medications, and treatment strategies for typical and severe migraine attacks. The literature review also provides information on the headache associated with personal protective equipment.